Sintesis Senyawa N-(2-Klorobenzoil)-N’-Fenilurea dan Uji Aktivitas Anti Kanker Terhadap Sel HeLa - Bambang Tri Purwanto (JURNAL ILMU KEFARMASIAN INDONESIA, 2018)
Research in the search for cancer drug compounds continue to be developed given the lack of specific anticancer compounds. Some urea derived compounds are also continuously being developed in search of potent anticancer compounds with minimal side effects. In relation to the above, we want to develop an urea derivative of N-phenylurea compound which will be reacted with benzoyl chloride derivative that is 2-chlorobenzoyl chloride so that N-(2-chlorobenzoyl) -N'phenylurea will be obtained. Synthesis of N- (2-chlorobenzoyl) -N'phenylurea was done by modified Schotten-Baumman method, then purity test was performed with thin layer chromatography using 3 different solvents. The next step is structural characterization using UV and IR spectrophotometry method, then 1H-NMR and MS spectrometry, so that the structure of N- (2-chlorobenzoyl) -N'phenylurea will be obtained. An anticancer activity test is performed on HeLa cells using MTT assay method and IC50 value will be obtained. Compounds that have been successfully synthesized are compound of N- (2-chlorobenzoyl) -N'phenylurea, with yield of 80.47% in the form of white needle crystal. The purity test of the N- (2-chlorobenzoyl) -N'phenylurea compound was performed by thin layer chromatography with 3 different solvents (hexan: ethyl acetate: methanol = 2: 3: 1; Hexan: acetone = 4: 2; Hexan: ethylacetate = 4: 2) a single stain is obtained which is different from the Rf value compared to the N-phenylurea origin compound. The Melting Point of the compound is 149oC so it is seen that the compound has been formed and different from the origin compound of N-phenylurea. The anticancer activity test after performed with MTT assay method using HeLa cells line, has an IC50 2100 mg / ml or 8,52 mM for the N- (2-chlorobenzoyl) -N'phenylurea and higher than hydroxy urea as standard compound which has the activity as 7537 mg / ml or 99,10 mM. Conclusion: N- (2-chlorobenzoyl) -N'phenylurea compound has been successfully synthesized and can be further developed as an anticancer compound. Keywords: Synthesis; N-(2-chlorobenzoyl)-N'phenylurea; anticancer activity; HeLa cells.